The Effectiveness of Introduction to Astronomy Teaching Materials to Improve Problem-Solving and Generic Science Skills - Pujani, N. M.; Arsana, K. G. Y.; Suma, K.; Selamet, K.; Erlina, N. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
This study aims to analyze the effectiveness of introductory astronomy teaching materials with inquiry settings on students' problem-solving and generic science skills. This study used a quasi-experimental design with the one-group pretest-posttest design. The research subjects were one class of 23 fourth-semester science education students. Data on problem-solving skills were collected using a test method with ten essay questions, and generic science skills data were collected using 30 multiple-choice questions. Data analysis was carried out descriptively, and a t-test with a significance level of 0.05. The analysis results showed that the use of inquiry-based introductory astronomy teaching materials in astronomy learning was effective in improving the problem-solving skills (p0.05, g = 0.67 medium categories) and generic science skills (p0 .05, g = 0.53 moderate type). So, it can be concluded that introductory astronomy teaching materials with inquiry settings effectively improve students' problem-solving and generic science skills.